Regional limb perfusion with antimicrobials in horses - Schade, Jackson; Curti, Juliana Massitel; Gonçalves, Gustavo Romero; Silva, Taise Pissinato da; Appolonio, Emanuel Vitor Pereira (Revista de Ciências Agroveterinárias, 2019)
Orthopedic infections are conditions commonly observed in horses, often affecting important structures such as bone and synovial tissue. Septic source conditions are extremely important in horses as they may result in permanent lameness caused by irreversible joint lesions. Therefore, treatments that result in higher concentrations of antimicrobials in infected areas act more effectively eliminating the bacterial population in these tissues. Therefore, the regional limb perfusion has proven to be an excellent alternative. This review addresses the main issues of regional limb perfusion with antimicrobials in horses. It will describe intravenous and intraosseous techniques, which involve the administration of an antimicrobial solution, in a part of the limb, previously isolated from the systemic circulation by applying a tourniquet. Regional perfusion has been described as a successful treatment for septic conditions at the distal region of the equine limb, since high concentrations of antimicrobial are achieved at the sites affected. In addition, it is easy to perform and presents a low risk of adverse systemic effects as well as reduced cost.